2015
DOI: 10.1097/opx.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corneal Thickness on the Penetration of Topical Vancomycin

Abstract: Corneal thickness does not influence the penetration of topically applied vancomycin into the anterior chamber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Similar results were reported in a study by Spierer et al that investigated the penetration of multiple administrations of vancomycin eye drops before cataract surgery in 58 patients with CCT between 458 μm and 635 μm [30]. Again, no significant difference of vancomycin concentration in the anterior chamber was found among patients enrolled in the study.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were reported in a study by Spierer et al that investigated the penetration of multiple administrations of vancomycin eye drops before cataract surgery in 58 patients with CCT between 458 μm and 635 μm [30]. Again, no significant difference of vancomycin concentration in the anterior chamber was found among patients enrolled in the study.…”
Section: Discussionsupporting
confidence: 87%
“…Corneal endothelial cell density showed similar results. Several clinical studies have reported no significant correlation between the corneal thickness and drug concentration in the aqueous humor [ 35 , 36 ]. A positive correlation was reported between corneal thickness and timolol concentration in the aqueous humor, but the correlation was weak [ 31 ].…”
Section: Discussionmentioning
confidence: 99%